The Antecedents and Consequences of Metacognitive Knowledge in Mathematics Learning: A Self-Determination Perspective - Tang, Yun; Wang, Xiaohan; Fang, Yu; Li, Jian (Frontiers in Psychology, 2021)
Grounded in the Self-Determination Theory and the Metacognitive and Affective Model of Self-Regulated Learning, this study investigated the longitudinal relationship of self-determined motivation as the antecedent and academic performance as the consequence of metacognitive knowledge (MK) in mathematics learning. Two waves of data were collected from senior high school students (N = 327) in the second semester in Grade 10 and Grade 11. A longitudinal mediation model was analyzed using structural equation modeling. Results revealed that autonomous motivation was positively related to MK of competence-enhancing strategies and negatively related to MK of avoidance strategies. Furthermore, mathematics performance was positively predicted by MK of cognitive/metacognitive strategies and negatively predicted by MK of avoidance strategies. The present study expands the understanding of MK and elaborates on the dynamics between MK, self-determined motivation, and mathematics performance. Especially, this study differentiates the MK of adaptive and maladaptive strategies and examines their motivational antecedents and academic effects. Our findings also suggest that autonomous motivation have longitudinal benefits on MK.